Safety aspect in installation of industrialized building system (IBS) formwork in Malaysian construction industry - Nur Izzati, Adnan (2018)
Emerging technology of Industrial Building System (IBS) has gained momentum as an intervention to improve the safety among workers. Safety aspect is very important must apply to any construction project to prevent accidence that resulting injury and fatalities. Installation of component IBS formwork is not excluding from having hazard. The goals of this paper are to study the process installation of IBS formwork, to identify the safety aspect and level of safety, and to identify the factors for improving safety in installation of IBS formwork. A total four process installation of IBS formwork which is lifting, placing, bracing and stripping process, and the relevant safety aspect that has to be applied during the process were identified in literature review. The findings disclosed six factors linked to the safety improvement of IBS construction site in Malaysia. The factors were historical, psychological, technical, procedural, organisational and the environmental factors. Structures of questionnaire was designed and distributed to the respondents with aim to assess their understanding and awareness regarding to the safety in installation IBS formwork. The viewpoint of practitioners in IBS construction including contractors and consultants was captured and collected through the quantitative approach. Returned questionnaire were analyses with used average index, frequency analysis method and mean. Result has shown respondent strongly agreed safety aspect need to apply is workers equipped with Personal Protective Equipment (PPE). The results also indicate that the safety is in good level at all phases. Furthermore, from the analysis, a psychological factor ranked as most crucial factor contributing to safer in installation IBS formwork. The psychological factor included the self-awareness and influences from workmates behaviour and least is environmental factor. To conclude, safety aspect is needed to apply. In order to improve safety of IBS formwork until zero accidents, a well trained and skilled workers are required for IBS construction, thus proper training is permissible and should be emphasised.